2019
DOI: 10.5222/mmj.2019.37929
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of General Anesthesia With Spinal Anesthesia In Laparoscopic Chlecystectomy Operations

Abstract: Objective: Laparoscopic cholecystectomy (LC) operations are being performed under general anesthesia (GA). Further studies are needed on the issue whether these operations can be performed under spinal anesthesia (SA). In this study we aimed to compare SA with (GA) in terms of efficacy and complications in patients who will undergo LC operations, and to investigate the effects of preemptive analgesia on the development of shoulder pain, transition to general anesthesia, and postoperative analgesia. Method: Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Remifentanil belongs to the current new type of opioid receptor agonist, with short action time, rapid onset of action, rapid recovery, and strong controllability. Also, the anesthesia drugs are eliminated faster in patients using remifentanil combined with propofol, which minimizes the impact of anesthetic drugs on the cognitive function and state of consciousness [21].…”
Section: Discussionmentioning
confidence: 99%
“…Remifentanil belongs to the current new type of opioid receptor agonist, with short action time, rapid onset of action, rapid recovery, and strong controllability. Also, the anesthesia drugs are eliminated faster in patients using remifentanil combined with propofol, which minimizes the impact of anesthetic drugs on the cognitive function and state of consciousness [21].…”
Section: Discussionmentioning
confidence: 99%
“…Intubating a single-lumen tube and placing a bronchial blocker in the right intermediate bronchus may enable ventilation of the right upper lobe and left lung while preventing PPV of the giant bulla. Although laparoscopic cholecystectomy is typically performed under general anesthesia and PPV, recent studies have shown that it can be performed safely under neuraxial block and spontaneous breathing [ 7 , 8 ]. Spinal anesthesia or combined spinal and epidural anesthesia with spontaneous breathing may have been a good alternative in our case.…”
Section: Discussionmentioning
confidence: 99%
“…These findings make SA an ideal technique for elective laparoscopic surgeries performed on low-risk patients with an American Society of Anesthesiologists (ASA) score of 1 or 2. SA not only facilitates faster patient recovery but also enables early discharge, ultimately leading to reduced costs [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%